If 1 8 + 3 0 8 + 1 5 + 1 0 4 = e a + f b + g c + h d ,where a , b , c , d , e , f , g , h are positive integers.Then find the value of a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution @shivamani patil . Can you prove that no other solutions exist? Thanks.
0verrated .......................................
There is some correction in the solution. You missed the letter e in the statement:
e a + f b + g c + h d = 1 1 + 7 + 1 3 + 2
good solution. I used reverse engineering from a past problem's solution.
Bro I can't believe youre 14. This is too clever. Cool!
First, we need to remove the square root sign to make it simpler to solve.
1 8 + 3 0 8
= 1 8 + 2 7 7
= 1 1 + 7 + 2 7 7
= ( 1 1 ) 2 + ( 7 ) 2 + 2 × 1 1 × 7
= ( 1 1 + 7 ) 2 = 1 1 + 7
Similarly, we will solve for the second one.
1 5 + 1 0 4
= 1 5 + 2 2 6
= 1 3 + 2 + 2 2 6
= ( 1 3 ) 2 + ( 2 ) 2 + 2 × 1 3 × 2
= ( 1 3 + 2 ) 2 = 1 3 + 2
So, 1 8 + 3 0 8 + 1 5 + 1 0 4 = 1 1 + 7 + 1 3 + 2
Therefore,
e a + f b + g c + h d = 1 1 + 7 + 1 3 + 2
Therefore, the answer is: a + b + c + d = 1 1 + 7 + 1 3 + 2 = 3 3
Problem Loading...
Note Loading...
Set Loading...
First we have
1 8 + 3 0 8 = 1 8 + 2 7 7 = 1 1 + 7 + 2 1 1 × 7 = ( 1 1 + 7 ) 2 = 1 1 + 7
Similarly
1 5 + 1 0 4 = 1 5 + 2 2 6 = 1 3 + 2 + 2 1 3 × 2 = ( 1 3 + 2 ) 2 = 1 3 + 2
Therefore
e a + f b + g c + h d = 1 1 + 7 + 1 3 + 2
Therefore a + b + c + d = 1 3 + 2 + 1 1 + 7 = 3 3